The Influence of Health Education About the Dangers of Smoking on the Knowledge of Adolescents in Lopang Domba Serang Village, Banten in 2022 - Riffa Ismanti; Sri mujiyanti; Tati Umayah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Smoking is a habit that is dangerous for both smokers themselves and others. Teenagers' insight regarding the dangers of smoking is very important so that they can prevent chronic diseases. The aim of this research is to determine the effect of health education regarding the dangers of smoking on adolescent knowledge. This research uses a quasi-experimental design with a one-group pretest posttest design. And using the paired t-test statistical test with a purposive sampling technique, with a sample size of 43 respondents. The average pretest result was 10.86, while the posttest average was 15.07. The result of the difference between the average knowledge of pretest and posttest teenagers is -4.209. The results of the paired t-test of adolescent knowledge obtained a p value ≤0.001. The conclusion of this research is that there is an influence of health education about the dangers of smoking on adolescent knowledge. Suggestions for managers in Lopang Domba Village to campaign about the dangers of smoking for health by collaborating with local health centers and putting up educational posters about the dangers of smoking